Paraplegia Inferior Tipe UMN sebagai Manifestasi Klinis pada Pasien Spondilitis dengan Penyebab Infeksi Nonspesifik: Laporan Kasus - Ni Wayan Ananda Hening Mayakosa (Unram Medical Journal, 2022)
Spondylitis with nonspecific infectious causes is a destructive infection of the spine or paraspinal structures due to nonspecific infectious agents. The development of spondylitis can result in destruction of the vertebrae and widespread inflammation into the epidural and paraspinal spaces. This can lead to spinal cord damage and other neurological complications, one of which is inferior paraplegia. The following is a case report of a 56-year-old man with clinical signs and symptoms and neurological deficits including low back pain with gradual onset, inferior paraplegia of the upper motor neuron (UMN) type with progressive gradual onset, and parahypoesthesia and parahypoalgesia at the level of the thoracic myelum segment 7. In the early stages of disease evaluation, these clinical signs and symptoms lead to a possible diagnosis of a myelum tumor with a differential diagnosis of tuberculous spondylitis. The results of bone tissue biopsy taken during surgery, it turned out that there was chronic inflammation that supported the diagnosis of infectious spondylitis with non-specific causes.